Her father's daughter : gender, power, and religion in the early Spanish kingdoms - Pick, Lucy K., 1966- (Cornell University Press, 2017)
"Considers a group of royal women in the early medieval kingdoms of the Asturias and of León-Castilla; their lives say a great deal about structures of power and the roles of gender and religion within the early Iberian kingdoms. Pick examines these women, all daughters of kings, as members of networks of power that work variously in parallel, in concert, and in resistance to some forms of male power, and contends that only by mapping these networks do we gain a full understanding of the nature of monarchical power"--